Baicalin Attenuates Allergic Rhinitis in Rats via Suppressing TLR4/AP-1 Inflammatory Signaling Pathway - Fengbo Yang; Fengjiao Li; Xing Chen; Ping Lv; Ruhui Xiao; Daxiong Ding; Qian Li (Journal of Animal and Plant Sciences, 2025)
Allergic rhinitis (AR) is a type of non-infectious inflammatory disease of the nasal mucosa with a complex pathogenesis. This study investigated the mechanism of Baicalin (BAI, main active component of Radix Scutellariae extract) on the immune-inflammatory response in AR rat model through Toll-like receptor 4 (TLR4)/activator protein-1 (AP-1) pathway. Healthy male Sprague-Dawley (SD) rats were used as Control group. The AR model (AR group) was constructed by ovalbumin sensitization, and treated with 0.9 mg/kg loratadine (LRD group) and 20, 40, 80 mg/kg of BAI (LD-BAI group, MD-BAI group and HD-BAI group)via intragastric administration for 28 days. Symptom scores of the rats were assessed, peripheral blood was collected to determine Th1/Th2 cell ratios and changes ininflammatory cytokines, and nasal mucosa tissues were harvested to analyze pathological morphological changes and the expression of proteins related to the TLR4/AP-1 signaling pathway. As against Control group, AR group suggested increased symptom scores; nasal mucosa tissue edema, congestion, and inflammatory cell infiltration; decreased CD3+CD4+IFN-γ+Th1 proportion and increased CD3+CD4+IL-4+Th2 proportion in peripheral blood; elevated levels of inflammatory cytokinesIgE, IL-4, IL-17, and TNF-α, and decreased levels of IL-10 and IFN-γ; increased relative expression (RE) of TLR4, Ikkβ, NF-κB, p-JNK, and AP-1 proteins in nasal mucosa tissue (P≤0.05). As against AR group, LRD group, LD-BAI group, MD-BAI group, and HD-BAI group all suggested visible improvements in symptom scores, nasal mucosa tissue morphology, peripheral blood immune cell ratios, immune cytokine levels, and the expression of TLR4 pathway-related proteins in nasal mucosa, with HD-BAI group (80 mg/kg) demonstrating the most significant improvements in all indicators (P≤0.05vs. AR group). These findings suggest that BAI may alleviate AR symptoms by modulating immune-inflammatory responses via TLR4/AP-1 signaling. BAI can suppress the activation of TLR4 and its downstream Ikkβ/NF-κB, JNK/AP-1 inflammatory signaling pathwaysin AR rat model. BAI shows the developing novel treatment modalities for AR, warranting further investigation.
Keywords: Allergic rhinitis; Baicalin; nasal mucosa; inflammatory cytokines; TLR4; Ikkβ/NF-κB; JNK/AP-1